Molecular Systematics of the Phoxinin Genus Pteronotropis (Otophysi: Cypriniformes). (31st May 2015) - Mayden, Richard L.; Allen, Jason S.
Abstract : The genus Pteronotropis is widely distributed along the gulf slope of eastern North America from Louisiana to Florida and rivers in South Carolina along the Atlantic slope. Pteronotropis have very distinctive, flamboyant coloration. The habitats most frequently associated with these species include heavily vegetated backwater bayous to small sluggish or flowing tannin-stained streams. Although Pteronotropis is recognized as a valid genus, no phylogenetic analysis of all the species has corroborated its monophyly. In recent years, four additional species have been either described or elevated from synonymy: P. merlini, P. grandipinnis, P. stonei, and P. metallicus, with the wide-ranging P. hypselopterus complex. To examine relationships within this genus and test its monophyly, phylogenetic analyses were conducted using two nuclear genes, recombination activating gene 1, RAG1, and the first intron of S7 ribosomal protein gene in both maximum parsimony and Bayesian analyses. In no analysis was Pteronotropis, as currently recognized, recovered as monophyletic without the inclusion of the currently recognized Notropis harperi, herein referred to as Pteronotropis . Two major clades are supported: one inclusive of P. hubbsi, P. welaka, and P. harperi and the second inclusive of P. signipinnis, P. grandipinnis, P. hypselopterus plus P. merlini sister to P. euryzonus, and P. metallicus plus P. stonei .